Two cannulated hip screws for femoral neck fractures: treatment of choice or asking for trouble? - Krastman, Patrick; van den Bent, Rob P.; Krijnen, Pieta; Schipper, Inger B. (Archives of orthopaedic and trauma surgery, 2006)
Undisplaced intracapsular fractures are predominantly treated with a minimally invasive fixation technique, whereas the standard treatment for displaced intracapsular fractures is still a subject of discussion. The purpose of this study was to identify the determinants influencing the outcome of intracapsular femoral neck fractures, treated with two cannulated hip screws. From January 1998 through December 2002 data of all consecutive patients with an intracapsular femoral fracture, treated with two cannulated screws, were documented. Consolidation was chosen as the primary endpoint, mortality and a reoperation for replacement of osteosynthesis were defined secondary endpoints. One hundred and twelve patients were included in the study. Fifty six percent of the intracapsular fractures healed within 1 year. Consolidation was accomplished in 95% of the stable fractures. Consolidation rates were negatively influenced by unstable fractures and inadequate anatomical reduction. The position of the screws did not influence consolidation rates. Reintervention rates were related to the number of local complications and the fracture type. In conclusion, the results of this study show that in case of operative treatment, undisplaced femoral neck fractures can be adequately fixated by two cannulated hip screws. Unstable, anatomically reduced femoral neck fracture (Garden III/IV) may be treated with a more stable implant (e.g. DHS) to avoid redisplacement. If adequate reduction cannot be achieved, endoprosthetic replacement is recommended.